Observation of a remarkable reduction of correlation effects in BaCr2As2 by ARPES - Nayak, Jayita; Filsinger, Kai; Fecher, Gerhard H.; Chadov, Stanislav; Minar, Jan; Rienks, Emile D. L.; Buechner, Bernd; Parkin, Stuart P.; Fink, Joerg; Felser, Claudia (Proceedings of the National Academy of Sciences of the United States of America, 2017)
The superconducting phase in iron-based high-Tc superconductors (FeSC), as in other unconventional superconductors such as the cuprates, neighbors a magnetically ordered one in the phase diagram. This proximity hints at the importance of electron correlation effects in these materials, and Hund’s exchange interaction has been suggested to be the dominant correlation effect in FeSCs because of their multiband nature. By this reasoning, correlation should be strongest for materials closest to a half-filled 3d electron shell (Mn compounds, hole-doped FeSCs) and decrease for systems with both higher (electron-doped FeSCs) and lower (Cr-pnictides) 3d counts. Here we address the strength of correlation effects in nonsuperconducting antiferromagnetic BaCr2As2 by means of angle-resolved photoemission spectroscopy (ARPES) and first-principles calculations. This combination provides us with two handles on the strength of correlation: First, a comparison of the experimental and calculated effective masses yields the correlation-induced mass renormalization. In addition, the lifetime broadening of the experimentally observed dispersions provides another measure of the correlation strength. Both approaches reveal a reduction of electron correlation in BaCr2As2 with respect to systems with a 3d count closer to five. Our results thereby support the theoretical predictions that Hund’s exchange interaction is important in these materials.
CRIS-Team Scopus Importer:2022-04-14
Keywords: ARPES; Correlated systems; Superconductivity; Transition metal pnictides